2019
DOI: 10.1080/15384101.2018.1560718
|View full text |Cite
|
Sign up to set email alerts
|

CUL4B regulates autophagy via JNK signaling in diffuse large B-cell lymphoma

Abstract: Aberrant expression of CUL4B was identified in various types of solid cancers. Cumulative evidences support the oncogenic role of CUL4B in cancers, including regulation of cell proliferation and signal transduction. However, its clinical value and potential pathogenic mechanism in diffuse large B-cell lymphoma (DLBCL) have not been described previously. Therefore, we hypothesize that overexpressed CUL4B may contribute to the pathogenesis of DLBCL. The aim of this study is to assess the expression and the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…IHC and H&E staining were operated according to the manufacturers’ instructions as previously illustrated [ 8 , 23 ]. Detailed information was shown in Supplementary methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IHC and H&E staining were operated according to the manufacturers’ instructions as previously illustrated [ 8 , 23 ]. Detailed information was shown in Supplementary methods.…”
Section: Methodsmentioning
confidence: 99%
“…All mice were randomly cohorted into two groups. As previously illustrated [ 8 , 23 ], DLBCL cells (either transfected with shSirt6 vectors or empty control vectors) were subcutaneously injected to SCID-beige mice to establish xenograft models ( n = 8 per group). Details are described in Supplementary methods .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Li et al demonstrated that Cullin4B (CULB4) (a scaffold protein of the CUL4B-RING E3 ubiquitin ligase complex, highly expressed in DLBCL) is implicated in the positive regulation of autophagy, thus contributing to DLBCL progression. CUL4B deletion leads to inhibition of proliferation, an effect that could be attributed to the pro-survival ability mediated by autophagy [100]. Pharmacological inhibition of autophagy or knockdown of LC3B, ATG5, or p62/SQSTM1 in DLBCL OCI-Ly1 cells inhibited cell proliferation and induced apoptosis in vitro [101].…”
Section: Autophagy In Chronic Lymphocytic Leukemia (Cll) and Lymphomamentioning
confidence: 99%
“…On the contrary, Li Y. et al observed a link between Cullin4B (CUL4B) (a scaffold protein of the CUL4B-RING E3 ubiquitin ligase complex, highly expressed in DLBCL) and autophagy in the positive regulation of DLBCL progression. They showed that CUL4B regulating autophagy occurred through JNK signalling and that the inhibition of proliferation induced by CUL4B deletion may be attributed to the blocking of the pro-survival ability mediated by autophagy [109]. This last study highlights the complexity of autophagy regulation in DLBCL and the necessity to improve our knowledge on the role of autophagy in lymphoma development.…”
Section: Autophagy and Lymphoid Tumoursmentioning
confidence: 99%